“Microbial Wars” in a Stirred Tank Bioreactor: Investigating the Co-Cultures of Streptomyces rimosus and Aspergillus terreus, Filamentous Microorganisms Equipped With a Rich Arsenal of Secondary Metabolites - Boruta, Tomasz; Ścigaczewska, Anna; Bizukojć, Marcin (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial co-cultivation is an approach frequently used for the induction of secondary metabolic pathways and the discovery of novel molecules. The studies of this kind are typically focused on the chemical and ecological aspects of inter-species interactions rather than on the bioprocess characterization. In the present work, the co-cultivation of two textbook producers of secondary metabolites, namely Aspergillus terreus (a filamentous fungus used for the manufacturing of lovastatin, a cholesterol-lowering drug) and Streptomyces rimosus (an actinobacterial producer of an antibiotic oxytetracycline) in a 5.5-liter stirred tank bioreactor was investigated in the context of metabolic production, utilization of carbon substrates and dissolved oxygen levels. The cultivation runs differed in terms of the applied co-culture initiation strategy and the composition of growth medium. All the experiments were performed in three bioreactors running in parallel (corresponding to a co-culture and two respective monoculture controls). The analysis based upon mass spectrometry and liquid chromatography revealed a broad spectrum of more than 40 secondary metabolites, including the molecules identified as the oxidized derivatives of rimocidin and milbemycin that were observed solely under the conditions of co-cultivation. S. rimosus showed a tendency to dominate over A. terreus, except for the runs where S. rimosus was inoculated into the already developed bioreactor cultures of A. terreus. Despite being dominated, the less aggressive strain still had an observable influence on the production of secondary metabolites and the utilization of substrates in co-culture. The monitoring of DO levels was evaluated as a fast approach of identifying the dominant microorganism during the co-cultivation process.